From Uncoordinated Patchworks to a Coordinated System: MERS-CoV to COVID-19 in Korea. Issue 6 (August 2020) - Kim, Yushim; Oh, Seong Soo; Wang, Chan
South Korea has experienced two national public health crises during this decade. The 2015 Middle East respiratory syndrome-coronavirus (MERS-CoV) response's failure to address coordination problems or authority conflicts provided an opportunity to revise its national disease control system before the 2020 coronavirus disease 2019 (COVID-19) crisis. Our reflection on Korea's MERS-CoV and COVID-19 responses provides a perspective on public health emergency management. It is difficult to project the scale of an emerging infectious disease in advance because of its contagious nature and ability to cross geographic boundaries. In a national epidemic or global pandemic, a centralized coordination effort at the national level is desirable, rather than fragmented local, city, or regional efforts.